2012
DOI: 10.1002/poc.2940
|View full text |Cite
|
Sign up to set email alerts
|

A computational study of the thermolysis of β‐hydroxy ketones in gas phase and in m‐xylene solution

Abstract: Theoretical calculations at the M05‐2X/6‐31+G(d) level of theory have been carried out in order to explore the nature of the mechanism of the thermal decomposition reactions of the β‐hydroxy ketones, 4‐hydroxy‐2‐butanone, 4‐hydroxy‐2‐pentanone, and 4‐hydroxy‐2‐methyl‐2‐pentanone in gas phase and in m‐xylene solution. The mechanism proposed is a one‐step process proceeding through a six‐membered cyclic transition state. A reasonable agreement between experimental and calculated activation parameters and rate co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…On the other hand, the metal chelation was modeled only in aqueous solution, because this is the relevant phase for ionic species. The M05-2X functional has been chosen because it is recommended for kinetic calculations by its developers, and its reliability has been independently confirmed by other authors. It is among the best performing functionals for kinetic calculations in solution, and for modeling reaction energies involving free radicals . The M05 functional was chosen for the Cu involving systems because it was parametrized including both metals and nonmetals, while M05-2X has double the amount of nonlocal exchange (2×) and was parametrized mainly for nonmetals.…”
Section: Computational Detailsmentioning
confidence: 99%
“…On the other hand, the metal chelation was modeled only in aqueous solution, because this is the relevant phase for ionic species. The M05-2X functional has been chosen because it is recommended for kinetic calculations by its developers, and its reliability has been independently confirmed by other authors. It is among the best performing functionals for kinetic calculations in solution, and for modeling reaction energies involving free radicals . The M05 functional was chosen for the Cu involving systems because it was parametrized including both metals and nonmetals, while M05-2X has double the amount of nonlocal exchange (2×) and was parametrized mainly for nonmetals.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The M05-2X functional was chosen because it is recommended for kinetic calculations by their developers, 35 and it has been successfully used by several independent authors to that purpose. [36][37][38][39][40][41][42][43] In a previous benchmark study it has also been demonstrated to be one of the best performing functionals for kinetic calculations of radicalmolecule reactions in solution. 44 The SMD solvent model has been chosen since its performance for describing solvation energies of both neutral and ionic species, in aqueous and also in non-aqueous solvents, is better than that achieved with other solvent models.…”
Section: Computational Detailsmentioning
confidence: 99%
“…All the electronic calculations were carried out by means of the Gaussian 09 package in the framework of DFT and TD-DFT. The exchange-correlation functional used for geometry optimizations and frequency calculations is M05-2X (global hybrid functional, with 56% HF exchange), as it is recommended for kinetic calculations by its developers, and its reliability has been independently confirmed by other authors. The standard 6-311+G** basis set of Pople and co-workers was used for all the atoms . The M05-2X functional has been chosen because it is among the best performing functionals for kinetic calculations in solutions and for calculating reaction energies involving free radicals .…”
Section: Computational Detailsmentioning
confidence: 99%